Ludwig: The Teacher - Valentinuzzi, Max E. (2012)
This is the third and last article of a series devoted to Carl Friedrich Wilhelm Ludwig's outstanding life (29 December 1816–23 April 1895). The first article portrayed him as a bioengineer [1] and the second as a physiologist [2]. Here, we view him as a teacher, the teacher par excellence, as recognized and commended by Theodor Beer (1866–1919)—a naturalist and physiologist who, incidentally, had a disgraced, sad, and ruined life [3]—making it a dramatic history subject, especially for its several human facets and controversial feelings and beliefs. In his own words: Ludwig war der deutsche Professor par excellence, der deutsche Professor im besten Sinne des Wortes, er war nicht nur tüchtig, sondern auch bedeutend, ein Klassiker in seiner Art.